The Relationship Between Psychological Capital and Teacher Career Commitment in Ethnic Areas of China: The Mediating Effects of Gratitude and Career Well-Being - Hu, Dong; Zhou, Tianmei; Zhou, Kaiji; Deng, Fang (Frontiers in Psychology, 2022)
The purpose of this study is to investigate the characteristics, relationships and mechanisms underlying the psychological capital, career commitment, gratitude and career well-being of teachers in ethnic areas. In total, 573 primary school and secondary school teachers in Sichuan Province (including 402 teachers in ethnic regions and 171 teachers in non-ethnic areas) were investigated. Following questionnaires were used to investigate these questions: “Psychological Capital Questionnaire for Primary and Secondary School Teachers,” “Gratitude Questionnaire,” “Teacher Career Well-being Questionnaire” and “Career Commitment Questionnaire for Primary and Secondary School Teachers.” The results show that the psychological capital of teachers in ethnic areas is higher than that of teachers in non-ethnic areas. Teachers in ethnic areas have lower levels of career well-being and lower levels of gratitude than teachers in non-ethnic areas. There was no significant difference in career commitment between teachers in ethnic areas and teachers in non-ethnic areas. There were significant positive correlations among psychological capital, gratitude, career well-being and career commitment. Psychological capital can predict career commitment significantly and positively. The mediating effect of career well-being between teachers’ psychological capital and career commitment was significant in both ethnic areas and non-ethnic areas. The chain of mediating effects between gratitude and career well-being was significant in non-ethnic areas. In conclusion, psychological capital can predict teacher career commitment effectively, and the prediction mechanism in ethnic areas is different from that in non-ethnic areas.